Star Trek discovery : the light of Kahless - Beyer, Kirsten; Johnson, Mike (Comic book author) (IDW Publishing, 2018)
"Uncover the secrets of the Klingon Empire with the diverse cast of the new Star Trek television show. Journey back in time to a decade before Captain Kirk and the Enterprise set out on their five-year mission, when the United Federatoin of Planets is locked in conflict with the mysterious Klingon Empire. But just who are these formidable foes?"--Page 4 of cover